MEASURING MUSLIM DECISIONS TO PURCHASE HALAL CERTIFIED PRODUCTS USING PLANNED BEHAVIOR THEORY - Muhammad Ardi; Mutiyah Mahdin; Srigandawati; Farhan Aditya; Dedi Kurniawan (Jurnal Ilmiah Al-Tsarwah, 2024)
This research modifies the theory of planned behavior in Muslim decision making in purchasing halal certified products among madrasah teachers and is the first research that is used as the object of research, namely madrasah teachers. The assumptions offered are: (1) attitudes, subjective norms, behavioral control and purchase intentions influence the decisions of madrasah teachers in Bone district buying halal certified products, (2) Finding out the magnitude of the direct and indirect influence on Muslims' decisions to buy halal certified food with the theory of planned behavior on madrasah teachers.  In achieving this goal, an inductive approach was used with a quantitative method in collecting data using a closed questionnaire technique via Google Form which was constructed using variables adopted from the theory of planned behavior by taking samples randomly from North Bone, city and South Bone areas which have schools. madrasa. The sample size criteria were adjusted to the analysis of the variance-based Structural Equation Modeling (SEM) approach with the partial Least Square (PLS) method. The required data is collected using observation methods, distributing questionnaires and documentation. The data that has been collected is analyzed quantitatively and the data that has been obtained through observation is expressed based on narrative. The research results show that the findings of this research show three things. First, attitude has no influence on the decision to buy halal-certified food, only Subjective norm and behavioral control variables have a direct influence on a person's decision to use halal products, especially among madrasah teachers in Bone Regency. Second, lack of literacy regarding purchasing decisions. Third, all variables when constructed through moderating variables to see the indirect influence have no influence on purchasing decisions.